2013
DOI: 10.1055/s-0033-1350794
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transport of 3,6′-Disinapoylsucrose, A Major Active Component of Polygala tenuifolia, Using Caco-2 Cell Monolayer and In Situ Rat Intestinal Perfusion Models

Abstract: 3,6'-Disinapoylsucrose is a major active component of the herb Polygala tenuifolia which has long been used for relieving tranquilization, uneasiness of the mind, and improving learning and memory. Our previous study found that 3,6'-disinapoylsucrose had a very low oral bioavailability. Its mechanisms of absorption in the small intestine have so far been unclear. In the present study, the absorption mechanisms of 3,6'-disinapoylsucrose were investigated by using the Caco-2 cell monolayer and in situ rat intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Both SDS and PLL greatly improved the transport of corilagin, GA, and EA. Other tight junction modulators such as EDTA and sodium caprate could enhance the transport of 3,6′-disinapoylsucrose [ 28 ]. These results further suggested that the paracellular transport appeared to be main limiting factor for the uptake of three compounds in Caco-2 cell monolayers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both SDS and PLL greatly improved the transport of corilagin, GA, and EA. Other tight junction modulators such as EDTA and sodium caprate could enhance the transport of 3,6′-disinapoylsucrose [ 28 ]. These results further suggested that the paracellular transport appeared to be main limiting factor for the uptake of three compounds in Caco-2 cell monolayers.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the DMEM culture medium was replaced with 150 μ L HBSS and incubated with different concentrations of fractions for 4 h. The concentration of PTF was ranged from 0.25 to 2 mg/mL. Thereafter, the HBSS was removed and the monolayers were incubated with 200 μ L of DMEM culture medium containing MTT 500 μ g/L for 4 h. Finally, the medium was removed, the formazan salt crystals that remained were dissolved with 150 μ L of DMSO and shaken for 10 min, and the absorbance was measured at 570 nm using microplate reader (Molecular Devices, Sunnyvale, CA, USA) [ 28 ]. The cell inhibitory rate was calculated as follows: inhibitory rate (%) = (A570 control − A570 sample )/(A570 control − A570 blank ) × 100%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the in vitro Caco‐2 cell model, single‐pass intestinal perfusion (SPIP) in situ model, and the everted intestinal sac in vivo model have been used frequently to study intestinal transport mechanisms (Chen et al, ; Hewei Li et al, ; Zhai et al, ). The SPIP in situ model provides optimal oral conditions in vivo for investigating the absorption potential of drugs in the intestine, and is used more commonly than other models (Bohets et al, ; Sutton, Rinaldi, & Vukovinsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…Malabsorption of compounds, due to low transport function, can effectively be improved by using a tight junction regulator (Bohets et al, ; Sutton et al, ). In many recent studies, verapamil was used as an inhibitor of P‐gp, indomethacin as an inhibitor of MRP2, reserpine as an inhibitor of BCRP, and EDTA as a tight junction regulator (Chen et al, ; Duan et al, ; Li et al, ). In our previous work, the mechanism for the synergistic effect of SDHD was clarified at the component–effect level.…”
Section: Introductionmentioning
confidence: 99%